Molecular detection and antibiogram of Salmonella spp. from apparently healthy Japanese quails of three different quail farms in Mymensingh - Jahan, Shamina; Zihadi, Md Asief Hossain; Nazir, K. H. M. Nazmul Hussain; Islam, Md. Shafiqul; Rahman, Md. Bahanur; Rahman, Marzia (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was carried out for the isolation, identification and antibiogram study of Salmonella spp. from apparently healthy Japanese quails (Coturnix japonica) at three different quail farms in Mymensingh, Bangladesh. Materials and methods: A total of 75 cloacal swab samples were randomly collected from apparently healthy Japanese quails from three different farms at Mymensingh, Bangladesh. The samples were subjected to a series of cultural and biochemical examination for the isolation of Salmonella followed by molecular detection by polymerase chain reaction (PCR). Motility of the Salmonella was performed by motility test and amplification of speF gene. The antibiogram profile of the isolates was also evaluated against commonly used antimicrobials by disc diffusion method. Results: The overall prevalence of Salmonella spp. in quails was found to be 13.33%(n=10/75). Out of the 10 isolates, seven were found to be motile. Farmwise, the prevalence of Salmonella spp. were 10%(n=3/30), 24%(n=6/25) and 5%(n=1/20) at the quail farms of Bangladesh Agricultural University (BAU), Shikarikanda and Akua, respectively. The antibiogram study revealed that all the isolates were resistant to both Erythromycin and Tetracycline. On the other hand, 100% isolates were sensitive to both Ciprofloxacin and Imipenem. Ninety percent isolates of Salmonella were resistant to Colistin sulphate. Neomycin was found to be sensitive to 80% Salmonella isolates. All the Salmonella isolates were found to be multidrug resistant (MDR). Conclusion: The presence of MDR Salmonella spp. in quails signifies public health importance of the organisms, which may be associated with food-borne illness. http://doi.org/10.5455/javar.2018.e248